KIBRA repairs synaptic plasticity and promotes resilience to tauopathy-related memory loss - Kauwe, Grant; Pareja-Navarro, Kristeen A.; Yao, Lei; Chen, Jackson H.; Wong, Ivy; Saloner, Rowan; Cifuentes, Helen; Nana, Alissa L.; Shah, Samah; Li, Yaqiao; Le, David; Spina, Salvatore; et al. (The Journal of clinical investigation, 2024)
Synaptic plasticity is obstructed by pathogenic tau in the brain, representing a key mechanism that underlies memory loss in Alzheimer's disease (AD) and related tauopathies. Here, we found that reduced levels of the memory-associated protein KIdney/BRAin (KIBRA) in the brain and increased KIBRA protein levels in cerebrospinal fluid are associated with cognitive impairment and pathological tau levels in disease. We next defined a mechanism for plasticity repair in vulnerable neurons using the C-terminus of the KIBRA protein (CT-KIBRA). We showed that CT-KIBRA restored plasticity and memory in transgenic mice expressing pathogenic human tau; however, CT-KIBRA did not alter tau levels or prevent tau-induced synapse loss. Instead, we found that CT-KIBRA stabilized the protein kinase Mζ (PKMζ) to maintain synaptic plasticity and memory despite tau-mediated pathogenesis. Thus, our results distinguished KIBRA both as a biomarker of synapse dysfunction and as the foundation for a synapse repair mechanism to reverse cognitive impairment in tauopathy.